Procedural success of transcatheter annuloplasty in ventricular and atrial functional tricuspid regurgitation - Barbieri, Fabian; Mattig, Isabel; Beyhoff, Niklas; Thevathasan, Tharusan; Romero Dorta, Elena; Skurk, Carsten; Stangl, Karl; Landmesser, Ulf; Kasner, Mario; Dreger, Henryk; Reinthaler, Markus (Frontiers in Cardiovascular Medicine, 2023)
Background Transcatheter annuloplasty is meant to target annular dilatation and is therefore mainly applied in functional tricuspid regurgitation (TR). Due to recent recognition of varying disease pathophysiology and differentiation of ventricular and atrial functional TR (VFTR and AFTR), comparative data regarding procedural success for both disease entities are required. Methods In this consecutively enrolled observational cohort study, 65 patients undergoing transcatheter annuloplasty with a Cardioband® device were divided into VFTR (n = 35, 53.8%) and AFTR (n = 30, 46.2%). Procedural success was assessed by comparing changes in annulus dilatation, vena contracta (VC) width, effective regurgitation orifice area (EROA), as well as reduction in TR severity. Results Overall, improvement of TR by at least two grades was achieved in 59 patients (90.8%), and improvement of TR by at least three grades was realised in 32 patients (49.2%). Residual TR of ≤2 was observed in 52 patients (80.0%). No significant differences in annulus diameter reduction [VFTR: 11 mm (9–13) vs. AFTR: 12 mm (9–16), p = 0.210], VC reduction [12 mm (8–14) vs. 12 mm (7–14), p = 0.868], and EROA reduction [0.62 cm2 (0.45–1.10) vs. 0.54 cm2 (0.40–0.70), p = 0.204] were reported. Improvement by at least two grades [27 (90.0%) vs. 32 (91.4%), p = 1.0] and three grades [14 (46.7%) vs. 18 (51.4%), p = 0.805] was similar in VFTR and AFTR, respectively. No significant difference in the accomplishment of TR grade of ≤2 [21 (70.0%) vs. 31 (88.6%), p = 0.118] was noted. Conclusion According to our results from a real-world scenario, transcatheter annuloplasty with the Cardioband® device may be applied in both VFTR and AFTR with evidence of significant procedural TR reduction.